Industrial Training Report: Perpustakaan Tun Seri Lanang (PTSL) UKM Bangi / Mohamad Asrul Fikri Mohamad Taupik - Mohamad Taupik, Mohamad Asrul Fikri (Faculty of Information Management, 2015)
This is the industrial training report that described all the experience gain from my industrial training session at "Perpustakaan Tun Seri Lanang, Universiti Kebangsaan Malaysia Bangi'' for five months period starting from the 2nd of February 2015 until the 30th of June 2015. There are four chapter in total of this industrial training report internship at "Persputakaan Tun Seri Lanang, Universiti Kebangsaan Malaysia, Bangi" for the past five months. The first chapter of this report were to describe detailed information about the organization that I has been placed for the industrial training. There were about the background of the organization, vision, mission, functions and many more. Besides that, the reader will be able to know what the collections are available at the organization and the facilities available at the organization that I was put for industrial training. On the second chapter of this industrial training report were to explain the organizational structures, departmental structures, and also the detailed information on the functions and objectives of each departments available in the organization. The third chapter of this industrial training report will be briefly explaining about all the training activities I was involved during my industrial training and all the special project that I was responsible on indexing data using the new system VALET and VITAL for digital materials. Finally on the last chapter I will explain on what I have gain the most during the industrial training for five months, the limitations and recommendations for the better improvement of this program.